PELAPISAN SOSIAL-BUDAYA PESISIR KELURAHAN MANGKANG KULON, SEMARANG - Kartika Dewi (Sabda: Jurnal Kajian Kebudayaan, 2018)
The purpose of this study is to identify economic conditions of the fishers and fish farmers and to understand the social stratification and work relation among the coastal society in Mangkang Kulon, a coastal area, with the main income almost entirely dependent on the sea and coast land. Social stratification is a society's categorization of people into socioeconomic strata, based upon their occupation and income, wealth and social status, or derived power (social and political). As such, social stratification is the relative position of person or group within a sociocultural system, category, geographic region, or social unit. Social stratification is the distinction of population or society into classes in multilevel classes (hierarchical); its manifestation is the presence of the upper class, middle class, and  lower class.Primary data were collected from the local fishers. Four fishers and two brackish water pond cultivators were in-depth interviewed. Secondary data (village monograph) were collected from the village office. Data were analyzed descriptively. There were three social stratifications found out and formed in the area of Rukun Warga I Mangkang Kulon based on the income among coastal society. First the upper strata, which consists of gogol tambak, second the middle strata which consists of tambak pandega, third the lower strata of individual petty fishers and tambak manual workers.